Avoiding blindness in managing epistaxis for a child with Duane's Retraction Syndrome. (November 2019) - Ahmadi, Navid; Huang, June; North, Hannah JD.; Lord, David; Cheng, Alan T.
Abstract: Duane's Retraction Syndrome (DRS), a congenital cranial dysinnervation disorder, accounts for 5% of all strabismus. A vascular anomaly in DRS, which became clinically relevant in the context of significant epistaxis, is presented. A 15-year-old girl with DRS underwent a rhinological procedure for traumatic nasal deformity and suffered large volume epistaxis. Using angiography, an anatomical variation was identified, noting the ophthalmic artery was supplied by branches from the sphenopalatine artery, facial artery, and middle meningeal artery; not from the internal carotid artery. Hence epistaxis control was achieved via alternative methods, and unilateral blindness was avoided.